(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sufism is a term used to describe Islam’s mystical tradition. Scholars generally agreed thatSufism and Islam were inseparable. Sufism has evolved into a global movement with adherents from everycorner of the globe. Many people have been influenced by the teachings of the Sufi saints, who haveshown them the route to God, away from the pleasures of this world. Sufi poetry and music from Punjabhas made a significant contribution to the spiritual upliftment of people all over the world. The words ofthe Sufi saints play an important part in Sufi poetry because Music speaks that words can’t, but this isespecially true when it comes to Sufi poetry. The manner in which these phrases are said may vary. Somewill be presented in Qawwali style, while others will be presented in Kafi style some will have atraditional aesthetic, while others will have a more western one. The core of Sufism should not be lost,no matter how these holy teachings are presented, regardless of the medium. God has bestowed manwith the invaluable gift of music.